Konflik dan wacana media dalam pembangunan gereja di Palembang: analisis jaringan diskursus - Oemar Madri Bafadhal; Erlisa Saraswaty; Adi Inggit Handoko (Faculty of Communications Science, Dr. Soetomo University, 2024)
Religious community relations in Indonesia require much attention as religious identity is frequently used to gain political power. One of the issues that is frequently politicised is the establishment of places of worship. The interrelationships of various groups that unite their power to become a force in legitimising the rejection of the establishment of places of worship must be investigated further. This study employed the Discourse Network Analysis technique to describe the discourse in the news reporting on establishing a church in Palembang. Twenty-five news stories from thirteen Palembang news portals were investigated, analysed using DNA and visualised using Visone. The findings show that various groups are involved, including church-building committees, community organisations, religious organisations, cultural organisations, political parties, and government institutions. The common argument is that the construction of houses of worship must be halted because it does not follow procedures. Political parties are central to this network. This implies that the relevant stakeholders could not keep the conflict out of politics. Meanwhile, the absence of parties who should have been present to maintain tolerance is an important entry point to ensure this does not happen again.